Exploring Students’ Perceptions toward MOOCs-Mediated Online Discussion Task among Indonesian University Students - Fitri Mulati, Dyah (Universitas Aisyah Pringsewu, 2022)
This article was designed as a case study surveyed twenty-nine students with master’s degrees from the English Education Department who have participated in Massive Open Online Courses (MOOCs) on the topic of Academic Writing by Canvas Network to investigate students’ perceptions toward MOOCs-Mediated specifically on Online Discussion Task. A questionnaire comprised five questions answering general information about participants and ten close-ended questions measuring perception of MOOCs-Mediated in an Online Discussion Task, and a semi-structured interview was conducted for collecting the data. Seventy-six percent of total students have never known of the MOOCs phenomenon nor did MOOCs mediated-online discussion tasks before participating in this lecturer’s task-based course while their reasons for participating in this course are for gaining knowledge, getting badges certificates, and following the lecturer’s assignment. The findings then denote that the participants have positive perceptions toward Online Discussion Tasks in MOOCs and regarded this activity as a future learning tool for their teaching and learning practice. This research has implications of being an example of having teaching and learning tools for blended learning way.